Clinical Identification of Tongue Cancer: A Case Report Series - Rochman Mujayanto; Fatimah Alaydrus; Ardiyan Cakra (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Dentists play an important role in oral cancer case finding. Dentists in the first line of healthcare can make identification through history taking and clinical examination. Case(s): The first case; a 40-year-old female complained of tongue ulcers sinces 2 months. The patient had articulation changes and clinical examination results of T2 N2a. The second case; 43-year-old male complained of tongue ulcers sinces 5 months. The patient had articulation changes and the clinical examination result was T2 N2a. The third case; 65-year-old male complained of tongue ulcers sinces 2 years. The patient had changes in articulation and clinical examination results T2 N2a. All patients were referred to an oncological surgeon. Conclusion: The change in the patient's voice, the discovery of extraoral lymphadenopathy (N), and the description of intraoral lesions (T), formed the basis of the patient's referral to an oncological surgeon.